As-RaD System as a Design Model of the Network Automation Configuration System Based on the REST-API and Django Framework - Adian Fatchur Rochim; Abda Rafi; Adnan Fauzi; Kurniawan Teguh Martono (Universitas Muhammadiyah Malang, 2020)
The use of information technology these days are very high. From business through education activities tend to use this technology most of the time. Information technology uses computer networks for integration and management data. To avoid business problems, the number of network devices installed requires a manageable network configuration for easier maintenance. Traditionally, each of network devices has to be manually configured by network administrators. This process takes time and inefficient. Network automation methods exist to overcome the repetitive process. Design model uses a web-based application for maintenance and automates networking tasks. In this research, the network automation system implemented and built a controller application that used REST API (Representational State Transfer Application Programming Interface) architecture and built by Django framework with Python programming language. The design modeled namely As-RaD System. The network devices used in this research are Cisco CSR1000V because it supports REST API communication to manage its network configuration and could be placed on the server either. The As-RaD System provides 75% faster performance than Paramiko and 92% than NAPALM.